PRANATA SOSIAL KEAGAMAAN DALAM LINGKUNGAN KELUARGA MUSLIM - Wartono Wartono (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
Reality diverse social life is a picture of the complexity of the problems facing religious social life and is traversed by humans. Humans are basically always wanted peace, happiness, tranquility and kesejahtera's. To achieve these objectives is not uncommon among them are successful and some that failed. The success achieved by man are not always able to carry and deliver a human on the nature of true happiness. That's because the new man can master limited tool life pursued and achieved limited keduniawiyan sheer, while behind the use of the tool life has been achieved through a lengthy process that can not touch the substance of real life.Social institutions per se is not something that is empirically, because there are elements that do not all have the physical embodiment. The elements of social institutions is not really human individuals, but the positions are occupied by those individuals and their rules of behavior, because humans in groups or social entities only as the executor function of the elements alone. So in reality they can come or go and be replaced by others without disturbing the existence and preservation of the social orderÂ Keywords: Pranata Sosial, Keluarga, Lingkungan